(3GdbGfhf GdhGLH GdJWHjb Ydi YbhO GdJLGQI GdGdcJQhfjI (B/s - (3GdefRdGhj, UGdMs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2088)
(3GdHGH GdGhd (B: (3eGgj YbhO GdJLGQI GdGdcJQhfjI JYQja YbhO GdJLGQI GdGdcJQhfjI, NUGFU YbhO GdJLGQI GdGdcJQhfjI, YbhO GdJLGQI GdGdcJQhfjI hefgL GdbhGYO GdeGOjI GdOhdjI, UYhHGJ JWHjb GdfWGb GdehVhYj dGJaGbjI GdGee GdeJMOI Ydi YbhO GdJLGQI GdGdcJQhfjI, UYhHGJ JWHjb GdfWGb GdOhdj hGdTNUj dGJaGbI GdGee GdeJMOI ddHjY Ydi YbhO GdJLGQI GdGdcJQhfjI GdHGH GdKGfj(B: (3GdbhGYO GdeGOjI ddJLGQI GdGdcJQhfjI GdeUGOQ GdbGfhfjI ddbhGYO GdeGOjI ddJLGQI GdGdcfQhfjI , Jbjje GdbhGYO ddJLGQI GdGdcJQhfjI GdbSe GdKGfj (B: (3YbhO GdJLGQI GdGdcJQhfjI hefgL bGYOI GdJfGRY GdOhdj ddbhGfjf (B. s
Keywords: (3GdJLGQI (B-(3JcfhdhLjG GdeYdheGJs; (3GdJLGQI GdNGQLjIs; (3GdbGfhf GdJLGQjs